PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS AUGMENTED REALITY UNTUK PENGENALAN ANATOMI GINJAL DAN JANTUNG MANUSIA - HUSADA, LUCKY JOPI; SUKIRMAN, SUKIRMAN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
The anatomy of the kidneys and heart is one of the topics studied in middle school science (IPA) subjects. However, most of the media used is still in the form of textbooks, which are less interactive and have limited visualization. This research aims to develop Augmented Reality (AR)-based learning media as a solution to these limitations. AR technology was chosen because it can provide interactive 3D visualizations, thereby enhancing students' learning experiences. The development uses the System Development Life Cycle (SDLC) model with a Waterfall approach, which includes needs analysis, planning, modeling, construction, and testing. Testing was conducted on 10 middle school students aged 13–14 years (4 males, 6 females), focusing on functionality, content, and ease of use. Overall, the testing showed that the application system works well, the material is easy to understand, and students did not face difficulties in operating it. Therefore, it can be concluded that this AR-based learning media can be used to study human kidney and heart anatomy. One limitation of this study is the small number of participants involved, so future research could be conducted with a larger sample size.